Design of an Aquarium Water Change System Based on Waterflow Sensor in PIAMARI Seawater Aquarium - Baswantara, Arif; Wibowo, Yuni Ari; Setiawan, Agus; Mujib, Muhammad (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2025)
Water exchange process is the one of the measures to maintain water quality in an aquarium. In addition to physical, chemical and biological treatment, regular water changes are a mechanism that must be carried out. The purpose of this research is to develop an automatic water exchange system, with the studies being carried out at Pangandaran Integrated Aquarium and Marine Research Institute (PIAMARI) seawater aquarium. This automatic water change system was constructed using an instrument based on water flow sensor and an ultrasonic sensor. The water flow sensor in the instrument functions as a water discharge reader which will controls the pump, either the drain pump or the filling pump. The ultrasonic sensor in the instrument then functions as a water level reader in the supply tank. Tests were carried out using the simulation method, where the aquarium water change system was run on a glass container resembling an existing seawater aquarium. The test results showed that the system worked well. The RMSE calculation gives values of 0.148 and 0.176 for the drain pump and values of 0.1 and 0.083 for the filling pump. These results show good performance of the sensors and pumps in the instrument, although there are shortcomings in the accuracy of the sensors. The evaluation found will be the next development of this system for larger scale utilization.Proses pergantian air merupakan salah satu upaya dalam menjaga kualitas air dalam suatu akuarium. Selain perlakuan fisik, kimia dan biologi, proses pergantian air yang rutin merupakan suatu mekanisme yang wajib untuk dilakukan, terutama pada aquarium air laut besar. Penelitian ini bertujuan untuk merancang suatu sistem pergantian air secara otomatis, dengan studi dilakukan pada akuarium air laut Pangandaran Integrated Aquarium and Marine Research Institute (PIAMARI). Sistem pergantian air otomatis ini dibangun menggunakan instrumen yang berbasis waterflow sensor dan ultrasonic sensor. Waterflow sensor pada instrumen berfungsi sebagai pembaca debit air yang selanjutnya akan mengontrol pompa, baik pada pompa kuras ataupun pompa isi. Ultrasonic sensor pada instrumen selanjutnya berfungsi sebagai pembaca muka air pada tangki suplay. Pengujian dilakukan dengan metode simulasi, dimana sistem pergantian air akuarium ini dijalankan pada wadah kaca menyerupai akuarium air laut yang ada. Hasil uji yang dilakukan menunjukkan bahwa sistem berhasil berjalan dengan baik. Perhitungan RMSE menunjukkan nilai 0,148 dan 0,176 pada pompa kuras serta nilai 0,1 dan 0,083 pada pompa isi. Hasil tersebut menunjukkan performa yang baik pada sensor dan pompa yang ada pada instrumen, meskipun terdapat kekurangan pada tingkat ketelitian sensor. Evaluasi yang ditemukan akan menjadi perkembangan selanjutnya dari sistem ini untuk pemanfaatan diskala yang lebih besar.